The key role of innovation and organizational resilience in improving business performance: A mixed-methods approach - Garrido-Moreno, Aurora; Martín-Rojas, Rodrigo; García-Morales, Víctor J. (International journal of information management, 2024)
An uncertain and complex economic environment requires companies to act quickly and reinvent their business strategies. Innovation has emerged as a strategic imperative to adapt to market changes and remain competitive, while resilience has gained attention as essential for organizations to respond successfully to external environmental pressures. Despite these strategic factors’ importance in unstable environments, little empirical research has analyzed them. Drawing on dynamic capabilities’ theory, our study examines the role of service innovation and organizational resilience in enhancing business performance using a sequential two-stage mixed-methods approach. First, a quantitative study was conducted to test the proposed research model using structural equation modelling (SEM) analysis with a sample of 343 service companies in Spain. Second, a qualitative analysis was performed with 12 interviews with managers to provide additional insights and a detailed understanding of the phenomenon. The results confirm innovation and resilience as key dynamic capabilities to address a changing business landscape and remain competitive. Our findings also reveal the strategic importance of digital tools (social media platforms) and external networks as drivers of service innovation. Managers can use these findings to leverage social media to engage in collaborative networks, enhance innovation and resilience, and succeed in turbulent markets. •Digital transformation is reshaping business strategies and innovation practices.•Mixed methods confirm innovation and resilience as key dynamic capabilities.•Social media and external networks are strategic drivers of innovation.•Findings provide a roadmap for business success in today's changing environment.